Thinking straight: the power, the promise, and the paradox of heterosexuality - Ingraham, Chrys (Routledge, 2005)
This collection of original essays will unravel the current heterosexual scene in two parts: one on rights and privileges, the other on popular culture. Topics covered include weddings, proms, citizenship, marriage penalties, cartoons, mermaids and myth.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; hétérosexualité; mariage; patriarcat; premier cycle; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis